Between Tradition and Modernity: Understanding Public Perceptions of Complementary and Alternative Medicine - Purboyekti, Sari (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study is to determine public perceptions of complementary and alternative medicine. Methodology: This research is quantitative with a descriptive design. The sample consisted of 88 residents of Pondok Benda Village, RW 013, Pamulang 2, using a random sampling technique. Data collection used a questionnaire developed by the researcher. Main Findings: The results of the study showed that 53.4% of respondents had a positive perception of complementary and alternative medicine, 62.6% had a positive perception of cupping, 60.2% of respondents had a positive perception of acupuncture and acupressure, the same number of respondents had a positive perception of reflexology, 80.7% of respondents had a positive perception of herbal medicine, 60.2% of respondents had a positive perception of bone fracture experts, 61.4% of respondents had a positive perception of shaman sembur, and 61.4% of respondents had a positive perception of the advantages and disadvantages of complementary and alternative medicine. Novelty/Originality of this study: The novelty of this research lies in revealing public perceptions of complementary and alternative medicine, a practice rarely studied in depth. This study provides new insights into the social, cultural, and belief factors that influence people's choices in using non-conventional medicine as an alternative or complement to modern medical treatment.